Legal Validity of the Ferienjob Internship Agreement in Indonesia: Keabsahan Hukum Perjanjian Magang Ferienjob di Indonesia - Indraputra P, Muhammad Chavelier; Mediawati, Noor Fatimah (Indonesian Journal of Law and Economics Review, 2025)
General Background: Internships serve as a bridge between academic learning and professional practice, helping students develop applied competencies. However, the emergence of the Ferienjob internship program in Germany involving Indonesian students has raised concerns about its legal compliance. Knowledge Gap: Previous studies have focused on the legal protection and rights of interns, yet few have examined the legality of international internship agreements that deviate from Indonesian law. Aim: This study analyzes the legal validity of the Ferienjob internship agreement under Indonesian positive law. Results: Findings reveal that the Ferienjob contract made by X Agency violates Article 1320 of the Indonesian Civil Code, lacks a lawful cause, and fails to meet essential and objective requirements, rendering it invalid. It also breaches key provisions in the Manpower Law, Permendikbud No. 3/2020, and Permentrans No. PER.08/MEN/V/2008. Novelty: This study identifies Ferienjob as a commercialized job market scheme, not an educational internship. Implications: Stronger legal supervision and institutional accountability are essential to prevent student exploitation in overseas internship programs. Highlights: Ferienjob violates Indonesian civil and manpower laws. The contract lacks lawful cause and balance between parties. Requires stronger supervision to protect student rights abroad. Keywords: Ferienjob, Internship Agreement, Positive Law, Legal Validity, Student Protection